2017
DOI: 10.1116/1.5004041
|View full text |Cite
|
Sign up to set email alerts
|

Spatial molecular layer deposition of polyamide thin films on flexible polymer substrates using a rotating cylinder reactor

Abstract: Polyamide thin films were rapidly grown using spatial molecular layer deposition (MLD) in a rotating cylinder reactor. The polyamide MLD films were coated on flexible metalized polyethylene terephthalate substrates using sequential exposures of trimesoyl chloride (TMC) and m-phenylenediamine (mPD). The rotating cylinder reactor was housed in a custom oven enclosure that maintained a constant temperature of 115 °C. One MLD cycle (TMC/mPD) was performed per rotation of the cylinder. Polyamide growth rates of 4.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…The same applies to organic and hybrid materials deposited by MLD, with encouraging initial results by spatial MLD, as discussed above. [67] Secondly, and as has been shown above, in some cases the use of plasma activation can contribute to an increase in the deposition rate and film quality. While atmospheric plasma has already been implemented for the deposition of oxides and metals with SALD, [68,143,150,[169][170][171] scaling up to large substrates will remain a technical challenge.…”
Section: -Outlook/perspectivesmentioning
confidence: 89%
See 2 more Smart Citations
“…The same applies to organic and hybrid materials deposited by MLD, with encouraging initial results by spatial MLD, as discussed above. [67] Secondly, and as has been shown above, in some cases the use of plasma activation can contribute to an increase in the deposition rate and film quality. While atmospheric plasma has already been implemented for the deposition of oxides and metals with SALD, [68,143,150,[169][170][171] scaling up to large substrates will remain a technical challenge.…”
Section: -Outlook/perspectivesmentioning
confidence: 89%
“…To date, SALD has been extensively used for encapsulation, to protect devices or to fabricate gas diffusion barriers, both in rigid and flexible substrates, including paper, as detailed below. [44,48,64,[66][67][68][69][70][71][72][73] Choi et al have demonstrated Al2O3 deposition rates as high as 7 nm/min (0.12 nm/s) at temperatures below 100 °C. The SALD system they have developed is coupled to a glove box and can coat substrates of industrial size (370 x 470 mm 2 ).…”
Section: Spatial Aldmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed report on the spatial reactor used in these depositions was previously reported. 22 The coating was deposited directly onto the as-prepared electrodes. Because of the nanoscale features and high aspect ratio in the electrodes, long precursor exposure times were needed to deposit a conformal coating on all surfaces within the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Deposition was performed in a custom-built spatial MLD system enclosed within a convection oven. The operation 22 and design 23 of this rotary drum system were previously described. The nitrogen purge gas (99.998%, Airgas) separating precursor dosing zones had a flow rate of 1000 sccm.…”
Section: Experimental Methodsmentioning
confidence: 99%